Tanggung Jawab Kurator Dalam Perkara Kepailitan Berdasarkan Prinsip Independensi - Sunaryo Sunaryo; Dina Haryati Sukardi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
The curator must be independent and not have a conflict of interest because the curator has such great authority over bankruptcy assets. The research used in this research is normative legal research. This is because researchers use library materials as data to analyze cases in the preparation of this study. provisions regarding the principle of independence are emphasized in the Code of Ethics of the Indonesian Curator and Administrator Association (AKPI) which states that in every appointment received, members of the Indonesian Curator and Administrator Association (hereinafter referred to as "members") must be independent and free from anyone's influence. Independence in bankruptcy law can be interpreted that the curator may not and cannot be intervened by anything, either by debtors, creditors, or other individuals within the bankruptcy institution or outside the bankruptcy institution. Independent also reflects the integrity of a curator which contains values including having a noble character, being trustworthy in carrying out his position, being able to act wisely and prudently in dealing with a plural reality between the interests of debtors and creditors, being consistent between his words and the responsibilities he carries, obeying the values and Norms, both written and unwritten, and no less important, are always oriented to the best interests of the bankruptcy estate.